Overnight RRP operations as a monetary policy tool: Some design considerations - Joshua Frost; Lorie Logan; Antoine Martin; Patrick McCabe; Fabio Natalucci; Julie Remache (Federal Reserve Bank of New York, 2015)
We review recent changes in monetary policy that have led to development and testing of an overnight reverse repurchase agreement (ON RRP) facility, an innovative tool for implementing monetary policy during the normalization process. Making ON RRPs available to a broad set of investors, including nonbank institutions that are significant lenders in money markets, could complement the use of the interest on excess reserves (IOER) and help control short-term interest rates. We examine some potentially important secondary effects of an ON RRP facility, both positive and negative, including impacts on the structure of short-term funding markets and financial stability. We also investigate design features of an ON RRP facility that could mitigate secondary effects deemed undesirable. Finally, we discuss tradeoffs that policymakers may face in designing an ON RRP facility, as they seek to balance the objectives of setting an effective floor on money market rates during the normalization process and limiting any adverse secondary effects.
Keywords: E52; E58; G21; G23; 330; repo; reverse repo; overnight RRP; monetary policy; interest on excess reserves; money market funds; Federal Reserve Board; Federal Reserve System